USE AND ABUSE OF PSYCHOACTIVE SUBSTANCES IN ACADEMIC PEOPLE AT A UNIVERSITY CENTRO NORTE GOIANO (CIPEEX, 2025)
Entering university is a challenging time for students, with various personal and academic challenges, which, combined with stress and anxiety, make individuals more vulnerable to the use and abuse of psychoactive substances and alcohol. The university environment is also related to increased consumption of these substances, which can cause harm and damage to academic performance and individual health. Given the relevance of the subject, research into university students and the profile of academic users of psychoactive substances and alcohol is essential, as knowing this profile allows us to target the possible development of policies that include treatment and prevention. This study aims to identify and outline the profile of psychoactive substance users among students at a university in north central Goiás. This is a field study, of a descriptive cross-sectional nature, with quantitative data analysis, on the premises of the Evangelical University of Goiás - Ceres Campus. It is a cross-section of the “umbrella” method, with questionnaires aimed at students aged between 18 and 40, enrolled at the institution who agree to take part in the research, with the signing of an informed consent form. The data obtained will be statistically analyzed to determine the prevalence of psychoactive substance and alcohol consumption among university students, as well as symptoms of anxiety and depression. This will help to broaden the debate on the subject, identify the pattern of consumption and promote preventive reflections on the use of drugs and alcohol during academic life.
Keywords: alcohol; young people; university; psychoactive; substances